The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1083/jcb.103.2.641
|View full text |Cite
|
Sign up to set email alerts
|

Vinculin interaction with permeabilized cells: disruption and reconstitution of a binding site.

Abstract: Abstract. Fluorescently labeled vinculin binds to focal contact areas in permeabilized cells independent of actin (Avnur, Z., J. V. Small, and B. Geiger, 1983, J. Cell Biol., 96:1622-1630, but the nature of the binding site is unknown. In this study we have examined the interaction of vinculin with these sites in permeabilized L6 myoblasts to define conditions that perturb the binding and subsequently to reconstitute it. Mild treatment with low concentrations of protease prevents vinculin incorporation witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…To specifically focus on associations with the CSK framework of the FAC, cells bound to beads were extracted with detergent (0.5% Triton X-100) in a CSK-stabilizing buffer to remove membranes and soluble cytosolic components before fixation. Past studies have shown that cellular proteins do not nonspecifically associate with the cytoskeleton when extracted with Triton under these conditions (Burr et al, 1980;Fey et al, 1984;Ball, 1986).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To specifically focus on associations with the CSK framework of the FAC, cells bound to beads were extracted with detergent (0.5% Triton X-100) in a CSK-stabilizing buffer to remove membranes and soluble cytosolic components before fixation. Past studies have shown that cellular proteins do not nonspecifically associate with the cytoskeleton when extracted with Triton under these conditions (Burr et al, 1980;Fey et al, 1984;Ball, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…The extraction buffers we used for FAC isolation were adapted from a CSK isolation procedure that was previously used to demonstrate that active pp6Ov-src associates with the CSK (Burr et al, 1980). The presence of calcium and magnesium in this buffer is required to preserve the structural integrity of the CSK as well as the FAC (Ball et al, 1986), however, it leaves open the potential for degradation of FACassociated molecules by cation-dependent proteases. For example, pp6Oc-src is a substrate for the calpain II (Oda et al, 1993), a calcium-dependent protease that has been reported to localize to the FAC (Beckerle et al, 1987).…”
Section: Many Signaling Molecules Are Enriched Within Isolated Facsmentioning
confidence: 99%
“…Another major finding of this study is the reconstitution and modulation by [Ca 2ϩ ] of the distribution of a partially reconstituted receptor complex in actin-depleted VPMs. Reconstitution of the binding of focal adhesion proteins to permeabilized or partially disrupted cells has been reported (Avnur et al, 1983;Ball et al, 1986). In our system we can test the binding of purified components to VPMs in which ␤1 receptors affinity for the ligand can be modulated.…”
Section: Discussionmentioning
confidence: 99%
“…The Triton X-100-soluble fraction was removed and the insoluble fraction, enriched in membrane-cytoskeletal complexes (Ben-Ze'ev et al, 1979) and adhesion plaques (Ball et al, 1986), was scraped into 1 ml of the same buffer. Equal volumes of the two fractions were analyzed by PAGE, followed by immunoblotting with the broad-range antivinculin antibody.…”
Section: Cell B'~actionation Immunoprecipitation and Pagementioning
confidence: 99%